What Drives Enrolment Gaps in Further Education? The Role of Beliefs in Sequential Schooling Decisions. (11th April 2019) - Belfield, Chris; Boneva, Teodora; Rauh, Christopher; Shaw, Jonathan
Abstract : We study students' motives to obtain sixth form and university education in a sample of 885 secondary school students in the UK. At each educational stage, perceptions about the consumption value of education explain a substantial share of the variation in students' intentions to obtain further education, while beliefs about the monetary benefits and costs are not found to play an important role. Beliefs about the consumption value of university predict not only students' intentions to go to university but also their intentions to go to sixth form, highlighting the importance of dynamic considerations in the choice. We further document that students' beliefs about the consumption value of further schooling strongly predict students' perceptions about how likely it is that they will obtain the necessary grades to proceed to the next educational stage. Differences in the perceived consumption value across gender and socioeconomic groups can account for a sizeable proportion of the gender and socioeconomic gaps in students' intentions to pursue further education as well as in their perceptions about their own performance.